The conflict of Kurdish political parties and their effects on social stability: An Analytical Study (Raparin Journal of Humanities (RJH), 2024)
The aim of this research is to find the impact of the conflicts on the political parties in the Kurdistan Region over the stability of the community, Also, showing the style and level of conflict of the political parties of Kurdistan region what role and roles do the political parties have in the community, There are some positive and negative effects on the official servants and the civil community, The existence of the political parties of Kurdistan region to what extent has been a place of trust and importance in the community. Then in the background of the research theory, the researcher reveals that, despite the severe conflict between the parties, the stability of the community is always under threat, and the same has been achieved. And in deep political conflict, there is always injustice in most aspects of the life of individuals and the community. Whenever there is a severe conflict between the parties, it will have impact on economical aspect and development. The severe political conflict affects the change of the community, instability, security, and instability of the people’s life. The existence of political conflict will have influence on the development of the cultural structure of the community (non-measure-anomi).